Outcome of permanent pacemaker implantation in transcatheter or surgical aortic valve replacement: A still unsolved problem. Issue 12 (21st September 2022) - Totaro, Antonio; Calafiore, Antonio Maria; Sacra, Cosimo; Testa, Gianluca
Abstract: Despite advances in technologies and clinical experience, conduction disorders, after transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR), represent the weak point of these procedures, requiring permanent pacemaker implantation (PPI) till 37.7% of patients in TAVR recipients. The role of PPI in TAVR and SAVR remains controversial in mid‐ and long‐term outcomes. Indeed, many studies have been published with contradictory results, leaving doubts rather than certainties.